2006
DOI: 10.1097/01.ede.0000190603.52867.22
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Misclassification in Studies of Agricultural Pesticides

Abstract: Our results demonstrate the importance of collecting type of pesticide formulation and suggest a generic exposure assessment is likely to result in appreciable exposure misclassification for many pesticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…When this algorithm was validated against urine concentrations of pesticides, moderate correlations were found with data from field observers, but for self-reported data correlations were low. Results differed by formulation of exposure (granular versus liquid), highlighting the importance of collecting information on type of pesticide [334]. To date (2010), only one study used prospectively assessed biomarkers [329].…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…When this algorithm was validated against urine concentrations of pesticides, moderate correlations were found with data from field observers, but for self-reported data correlations were low. Results differed by formulation of exposure (granular versus liquid), highlighting the importance of collecting information on type of pesticide [334]. To date (2010), only one study used prospectively assessed biomarkers [329].…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…Study participants are often relied upon to recall the name(s) of specific pesticides used, number of days of specific pesticide application, type of application equipment that was used, use of personal protective devices, number of acres farmed and typical personal hygiene practice. 164,165 An analysis of biological marker data from participants in the Farm Family Exposure Study showed that internal exposure levels varied by specific type of chemical and the degree of direct contact with the application process. 166 Studies with inferred exposure based on farming occupations or on exposure defined generally as ''pesticides'' or ''herbicides'' are less informative than studies that evaluate specific chemicals.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%
“…In the AHS, self-reported LDs and IWLDs of pesticide exposure are used as the primary exposure measures. To date, four studies have examined the validity of the intensityweighted exposure algorithm used in the AHS (Acquavella et al 2006;Coble et al 2005;Thomas et al 2009). Two of these studies were conducted using data from the Pesticide Exposure Assessment Study conducted in Canada (Acquavella et al 2006;Coble et al 2005), and the remaining two studies were conducted using members of the AHS cohort Thomas et al 2009).…”
Section: Pesticidementioning
confidence: 99%
“…To date, four studies have examined the validity of the intensityweighted exposure algorithm used in the AHS (Acquavella et al 2006;Coble et al 2005;Thomas et al 2009). Two of these studies were conducted using data from the Pesticide Exposure Assessment Study conducted in Canada (Acquavella et al 2006;Coble et al 2005), and the remaining two studies were conducted using members of the AHS cohort Thomas et al 2009). In general, validation studies have observed low to moderate correlations between exposure intensity algorithm scores and urinary biomarkers of 2,4-D, 4-chloro-2-methylphenoxyacetic acid (MCPA), captan, glyphosate, and chlorpyrifos (Acquavella et al 2006;Coble et al 2005;Thomas et al 2009).…”
Section: Pesticidementioning
confidence: 99%